Digital Healthcare Intervention to Improve Self-Management for Patients with Type 2 Diabetes: A Scoping Review - Nadia Villalobos; Francisco Serna Vela; Luis Morales Hernandez (Journal of Scientific Innovation in Medicine, 2020)
Nowadays, diabetes is considered to be one of the major health emergencies worldwide. Products and services for diabetes management have been evolving into digital platforms and tools. We conducted a scoping review on intervention research to identify the benefits, barriers and limitations during the intervention. Our research identified 115 studies that were relevant for the study using the keyword research strategy; 25 met our inclusion criteria. These studies focus on the communication between health professionals and their patients; and self-care behavioral changes caused by using digital tools such as mobile-phones, apps, web-portals and Bluetooth devices to keep track of the patient’s health data. The benefits of using eHealth systems are: raising awareness among patients, tracking their health data, and acquiring self-care behaviors alongside the health professional and family members. Future research needs to improve the user experience avoiding the identified barriers like 'frustration technology, lack of face-to-face intervention' and 'low health literacy' to prevent patients from abandoning the intervention.